Changes in Forest Conditions in a Siberian Larch Forest Induced by an Extreme Wet Event - Aleksandr Nogovitcyn; Ruslan Shakhmatov; Tomoki Morozumi; Shunsuke Tei; Yumiko Miyamoto; Nagai Shin; Trofim C. Maximov; Atsuko Sugimoto (Forests, 2022)
The taiga forest, a semi-arid and nitrogen-limited ecosystem on permafrost, has changed under extreme wet events. This study aims to understand the changes that occurred in a larch forest in Eastern Siberia after the wet event of 2006–2007. In the summer of 2018, studies were conducted at the Spasskaya Pad Experimental Forest Station near Yakutsk, Russia, where a transect (60 m × 510 m) with 34 plots (30 m × 30 m) was set. It included intact sites and affected sites with different levels of forest damage, owing to the extreme wet event. We observed spatial variations in the normalized difference vegetation index (NDVI) calculated from Landsat satellite-observed data, and the foliar δ13C, δ15N, and C/N (carbon/nitrogen) ratio obtained from the needle samples of 105 mature larch trees. Our results reveal that the affected plots had a lower NDVI than the intact plots, resulting from a difference in tree stand density. In addition, the stand density is suggested to be a controlling factor in the spatial variations in the foliar C/N and δ13C values based on their significant relationships with the NDVI in June. We concluded that the larch trees from the regenerating forests in the affected areas have a higher nitrogen level and light availability (relatively low C/N and high δ13C) because of the slight competition for resources, owing to a low-stand density. This may lead to further succession of the larch forests after the extreme wet event.